An experimental examination of foam stability under pressure for EPB TBM tunneling. (July 2018) - Wu, Yuanli; Mooney, Michael A.; Cha, Minsu
Abstract: Foam as a soil conditioning agent has been extensively employed in earth pressure balanced (EPB) tunnel boring machines (TBM) to change the mechanical and hydraulic properties of soils for effective excavation. Foam stability is a critical parameter that influences the performance of foam and foam-conditioned soils. This paper examines foam stability under pressure through a novel foam generation – pressure chamber – foam capture testing system. A comprehensive suite of foam experiments was performed to examine the physical phenomenon of foam degradation and time-dependent foam properties under pressure. Testing results suggest that foam liquid loss is not an effective indicator for characterizing foam stability, while foam volume loss is a more appropriate measure of foam stability. Results also reveal that foam liquid drainage is significantly retarded at higher chamber pressure because foam bubbles are smaller and more uniform. Bubble size was not appreciably different in dry and wet foams.